2006
DOI: 10.1577/a05-042.1
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Channel Catfish Growth after Two Generations of Selection and Comparison of Performance Traits among Channel Catfish, Blue Catfish, and Hybrid Catfish Fingerlings in an Aquarium Rack System

Abstract: Abstract.-A 9-week growth study was conducted to compare the fingerling performance of two genetic groups of channel catfish Ictalurus punctatus (U.S. Department of Agriculture [USDA] 103 and USDA303) with that of blue catfish I. furcatus and their hybrid in an aquarium rack system. Fish of approximately 20 g were randomly selected from multifamily populations and acclimated to the aquarium rack system for 2 weeks prior to the start of the 9-week study. Differences in growth indices, feed and protein efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…However, when final weight was added as a covariate in the statistical model, body composition indices were similar among the four genetic groups. Small (2006) also found a tendency toward lower protein content and higher fat content for USDA103 and USDA303 catfish when compared to hybrid and blue catfish at the end of a 9‐wk study. As in the current study, Small (2006) used final weight in the statistical analysis and found that mean body composition indices were not significantly different among the four strains of fish.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, when final weight was added as a covariate in the statistical model, body composition indices were similar among the four genetic groups. Small (2006) also found a tendency toward lower protein content and higher fat content for USDA103 and USDA303 catfish when compared to hybrid and blue catfish at the end of a 9‐wk study. As in the current study, Small (2006) used final weight in the statistical analysis and found that mean body composition indices were not significantly different among the four strains of fish.…”
Section: Discussionmentioning
confidence: 79%
“…This would suggest that the USDA102 fish were not as efficient as the other three strains in converting feed and dietary protein to weight gain. In a study comparing USDA103 and USDA303 strains, Small (2006) also found that PER and NR were similar between these two strains of fish.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, the initial size differences appear to have a genetic basis. In addition, USDA103 channel catfish lines typically have superior early growth compared with other catfish lines in both pond and tank trials (Li et al 1998; Li et al 2001; Bosworth et al 2004; Small 2006; Peterson et al 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…(since the system operating implies no sedimentation, no waste discharge, and no N gaseous lost) where, in the overall circuit: A bibliographic approach was employed in the nitrogen (N) budget assessment, using the Channel Catfish, Ictalurus punctatus Rafinesque, 1818 (a siluriform comparable to P. punctifer), N retention (%) of N consumed (Small, 2006), the tilapia (cichlid) N retention (%) of N consumed (Beveridge et al, 1991), and the N composition of Chlorella sp. (Gilles et al, 2013).…”
Section: Study Periodsmentioning
confidence: 99%
“…Evaluation of the nitrogen budget during the second period The N amount included in the food was 455 g, 165.4 g of which was retained by P. punctifer and 289.4 g excreted, using the Channel Catfish retention rate (Small, 2006). On the basis that N excreted by P. punctifer was retained by sewage fish, directly eating feces, dead algae, and bacteria, and indirectly consuming dissolved N (urine), then using a retention rate of 43% (Beveridge et al, 1991), the N amount retained by the sewage fish was 136.0 g, and 153.4 g excreted.…”
Section: First Study Periodmentioning
confidence: 99%